Numerical modelling of abdominal aortic aneurysm - Taib, Iskriza (Penerbit UTM, 2007)
Abdominal aortic aneurysm is a bulging and widening of the blood vessel due the weakening of aortic wall which may prone to rupture of aneurysm. Normally, in clinical practice, surgical treatment of AAA is considered after the maximal diameter exceeds 5-6 cm (Lederle et al., 2002). Nevertheless, the increasing of the aneurysm region may eventually increase the risk of rupture (Szilagyi et al., 1972) although, rupture could occur in a small aneurysm (Lederle et al., 2002). To study deeper in detection of aneurysm rupture, both of non-geometric patient characteristic and geometric properties should be considered (Hatakeyama et al., 2001). In recent study, computational model of mechanical behaviour in AAA is most prominent trend in AAA rupture risk assessment through the improvement of imaging and segmentation (Stringfellow et al., 1987). There are two available treatment open surgery and Endovascular aneurysm repair (EVAR) (Rafiq et al., 2007). EVAR is gaining the popularity rather than open surgery due the minimally invasive technique. In EVAR, the stent was guided to disease aorta and then the ballooning catheter inflated in order to create new sleeve which would protecting the weaken wall from the pulsatile blood flow (Burt et al., 2006 and Borovetzet et al., 2004). Two shapes of aneurysm have been identified; saccular and fusiform. The existing treatment procedures of fusiform aneurysm do not provide the suitability (Jou et al., 2003), therefore, the stent becomes an experimental alternative for these aneurysm.